Comparison of Blood Homocysteine Levels between Women with Recurrent Pregnancy Loss and Women with Normal Fertility (Journal of Enam Medical College, 2023)
Background: Recurrent early pregnancy loss is a common but frequently unexplained obstetric problem. As it happens in early weeks of pregnancy, abnormal vasculogenesis and disordered cell multiplication are possible causes. Hyperhomocysteinemia is associated with both these pathological processes.Objective: To assess the association between hyperhomocysteinemia and recurrent pregnancy loss.Materials and Methods: This case-control observational study was conducted in the Department of Gynaecology and Obstetrics of Bangabandhu Sheikh Mujib Medical University, Dhaka during January to December 2015. Sixty patients were divided into two groups: 30 with recurrent pregnancy loss (RPL) as cases and 30 normal healthy mothers as controls.Results: All the subjects were matched in terms of age (p = 0.504). All were within normal BMI range (19.5 to 25 kg/square meter). Subjects in both groups were comparable in height, weight and BMI. 33.3% women of control group were in the low income stratum (monthly income 20000 taka or less) compared to50% of the RPL group. Control group had an equal mix of educational level from below Secondary School to Post-Graduates whereas there were fewer Post Graduate patients (3.3%) in the RPL group compared to control group (23.3%). The frequency of hyperhomocysteinemia (>15 micromoles/L) was significantly higher in cases compared to controls (46.7 vs.16.7%, p= 0.012). Mean homocysteine level was also significantly higher in cases compared to controls (13.67+/-4.80 vs. 9.87+/-4.84 micromole/L; p= 0.003).Conclusion: This study shows that blood homocysteine level in recurrent pregnancy loss patients is significantly higher compared to normal fertile mothers. There is a strong association between hyperhomocysteinemia and RPL.J Enam Med Col 2021; 11(1): 10-17